Genetic Evaluation and Use of Chromosome Microarray in Patients with Isolated Heart Defects: Benefits and Challenges of a New Model in Cardiovascular Care - Helm, Benjamin M.; Freeze, Samantha L. (Frontiers in Cardiovascular Medicine, 2016)
Congenital heart defects (CHD) are common birth defects and result in significant morbidity and global economic impact. Genetic factors play a role in most CHD, however, identification of these factors has been historically slow due to technological limitations and incomplete understanding of impact of human genomic variation on normal and abnormal cardiovascular development. The advent of chromosome microarray (CMA) brought tremendous gains in identifying chromosome abnormalities in a variety of human disorders and is now considered part of a standard evaluation for individuals with multiple congenital anomalies and/or neurodevelopmental disorders. Several studies investigating use of CMA found that this technology can identify pathogenic copy-number variations in up to 15-20% of patients with CHD with other congenital anomalies. However, there have been fewer studies exploring the use of CMA for patients with isolated CHD. Recent studies have shown that the diagnostic yield of CMA in individuals with seemingly isolated CHD is lower than in individuals with CHD and additional anomalies. Nevertheless, positive CMA testing in this group supports chromosome variation as one mechanism underlying the development of isolated, non-syndromic CHD—either as a causative or risk-influencing genetic factor. CMA has also identified novel genomic variation in CHD, shedding light on candidate genes and pathways involved in cardiac development and malformations. Additional studies are needed to further address this issue. Early genetic diagnosis can enhance the medical management of patients and potentially provide crucial information about recurrence. This information is critical for genetic counseling of patients and family members. In this review, we review CMA for the non-genetics cardiology provider, offer a summary of copy-number variation in isolated CHD, and advocate for the use of CMA as part of the cardiovascular genetics evaluation of patients with isolated CHD. We also provide perspective regarding the benefits and challenges that lie ahead for this model in the clinical setting.